Pilot study on the influence of acute alcohol exposure on biophysical parameters of leukocytes - Shalchi-Amirkhiz, Puya; Bensch, Tristan; Proschmann, Undine; Stock, Ann-Kathrin; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Molecular Biosciences, 2023)
This pilot study explores the influence of acute alcohol exposure on cell mechanical properties of steady-state and activated leukocytes conducted with real-time deformability cytometry. Nineteen healthy male volunteers were enrolled to investigate the effect of binge drinking on biophysical properties and cell counts of peripheral blood leukocytes. Each participant consumed an individualized amount of vodka to achieve a blood alcohol concentration of 1.2 ‰ as a mean peak. In addition, we also incubated whole blood samples from healthy donors with various ethanol concentrations and performed stimulation experiments using lipopolysaccharide and CytoStim™ in the presence of ethanol. Our findings indicate that the biophysical properties of steady-state leukocytes are not significantly affected by a single episode of binge drinking within the first two hours. However, we observed significant alterations in relative cell counts and a shift toward a memory T cell phenotype, akin to changes observed during immunosenescence. Moreover, exposure to ethanol during stimulation appears to inhibit the cytoskeleton reorganization of monocytes, as evidenced by a hindered increase in cell deformability. Further cell mechanical analyses of immune cells are needed, to explore the potential of biophysical properties as potential biomarkers or prognostic indicators for alcohol-related changes in the immune system.